Hole localization in bulk and 2D lead-halide perovskites studied by time-resolved infrared spectroscopy - Sandner, Daniel; Sun, Kun; Stadlbauer, Anna; Heindl, Markus W.; Tan, Qi Ying; Nuber, Matthias; Soci, Cesare; Kienberger, Reinhard; Müller-Buschbaum, Peter; Deschler, Felix; Iglev, Hristo (Journal of the American Chemical Society, 2024)
Scattering and localization dynamics of charge carriers in the soft lattice of lead-halide perovskites impact polaron formation and recombination, which are key mechanisms of material function in optoelectronic devices. In this study, we probe the photoinduced lattice and carrier dynamics in perovskite thin films (CsFAPbX3, X = I, Br) using time-resolved infrared spectroscopy. We examine the CN stretching mode of formamidinium (FA) cations located within the lead-halide octahedra of the perovskite structure. Our investigation reveals the formation of an infrared mode due to spatial symmetry breaking within a hundred picoseconds in 3D perovskites. Experiments at cryogenic temperatures show much-reduced carrier localization, in agreement with a localization mechanism that is driven by the dynamic disorder. We extend our analysis to 2D perovskites, where the precise nature of charge carriers is uncertain. Remarkably, the signatures of charge localization we found in bulk perovskites are not observed for 2D Ruddlesden-Popper perovskites ((HexA)2FAPb2I7). This observation implies that the previously reported stabilization of free charge carriers in these materials follows different mechanisms than polaron formation in bulk perovskites. Through the exploration of heterostructures with electron/hole excess, we provide evidence that holes drive the formation of the emerging infrared mode.
Gesehen am 09.12.2024